2019
DOI: 10.1590/s1983-41952019000400011
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of reinforced concrete beams using Solver tool

Abstract: Due to the development in structural analysis studies, optimization techniques have become part in the design of reinforced concrete structures. Making it possible to design structures with optimized cross-sections. Thus, the present study aims to implement optimization techniques, using the Solver tool, to design procedure of reinforced concrete beams following the precepts of Brazilian Standard ABNT NBR 6118:2014. Focusing to minimize the cost of reinforced concrete beams, where the design variables are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The optimization techniques investigated include the firefly algorithm [ 15 ], simulated annealing [ 13 , 16 , 17 ], and genetic algorithm [ 18 , 19 , 20 ]. Several studies used different algorithms built in the solver tool provided by Microsoft Excel [ 12 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization techniques investigated include the firefly algorithm [ 15 ], simulated annealing [ 13 , 16 , 17 ], and genetic algorithm [ 18 , 19 , 20 ]. Several studies used different algorithms built in the solver tool provided by Microsoft Excel [ 12 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies focused on the optimization of individual RC structural elements, such as slabs [ 13 , 23 , 24 ], beams [ 12 , 18 , 22 ], columns [ 15 , 16 , 25 ], footings [ 21 , 26 , 27 ], and retaining walls [ 19 , 28 , 29 ]. The design procedures in these studies were subjected to specific code restrictions, such as the American concrete institute (ACI 318-19, ACI 318-14, ACI 318-05), Indian standards (IS: 456), Eurocode 2 (EN 1992-1-1:2004/A1:2014), and Brazilian standards (ABNT NBR 6118:2014, ABNT NBR 6118:2007).…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of reinforced concrete structures considering standard design constraints have been already studied in some papers from the literature [9], [13], [15], [19], [20]. In the context of the Brazilian design standard, some studies have also been developed, for example, Bordignon and Kripka [28], Medeiros and Kripka [29], [30], Kripka et al [31] and Correia et al [32]. However, there is a lack in studies that discuss the characteristics of the optimal structures found and their relationships with the design constraints.…”
Section: Introductionmentioning
confidence: 99%
“…To increase competitiveness, companies invest in new production technologies, materials, and waste reduction methods, which allows reducing the total cost of the investment project and obtaining a significant economic effect on the implementation of construction projects [3,4]. Due to the high level of development of computer technology in construction, complex structures are calculated using software, resulting in a cost-effective method of designing buildings and structures [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization methods allow the designer to make a choice from a set of possible solutions to an engineering problem and make an optimal decision, reducing the project development period. In practice, optimization problems are solved using universal software such as MATLAB, Octave, Scilab, Dakota, Solver and other software systems [2,6]. At the same time, the universal software for solving optimization problems is not fully suitable for solving particular industry-specific problems of designing facilities in construction, created in the form of computer graphic three-dimensional, parametric objects using Building Information Modelling (BIM).…”
Section: Introductionmentioning
confidence: 99%